Molecular epidemiology of peste des petits ruminants virus in West Africa: Is lineage IV replacing lineage II in Burkina Faso? - Biguezoton, A.S.; Ilboudo, Guy S.; Wieland, Barbara; Sawadogo, R.W.-Y.; Dah, F.F.; Sidibe, C.A.K.; Zoungrana, A.; Okoth, Edward A.; Dione, Michel M. (MDPI, 2024)
This study aimed at investigating the genetic lineages of peste des petits ruminants virus (PPRV) currently circulating in Burkina Faso. As part of PPR surveillance in 2021 and 2022, suspected outbreaks in different regions were investigated. A risk map was produced to determine high-risk areas for PPR transmission. Based on alerts, samples were obtained from three regions and all sampled localities were confirmed to fall within PPR high risk areas. We collected swab samples from the eyes, mouth, and nose of sick goats. Some tissue samples were also collected from dead animals suspected to be infected by PPRV. In total, samples from 28 goats were analysed. Virus confirmation was performed with RT-PCR amplification targeting the nucleocapsid (N) gene. Partial N gene sequencing (350 bp) was carried out using the RT-PCR products of positives samples to characterise the circulating lineages. Eleven sequences, including ten new sequences, have been obtained. Our study identified the presence of the PPRV lineage IV in the three studied regions in Burkina Faso with a genetic heterogeneity recorded for the sequences analysed. Previously published data and results of this study suggest that PPRV lineage IV seems to be replacing lineage II in Burkina Faso.